Speech rehabilitation method to improve verbal fluency in childhood stuttering (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: through an exhaustive review of scientific evidence, this research aims to estab-lish the most efficient method to improve verbal fluency in childhood stuttering. METHODS: sys-tematic review using various search strategies in various databases, contacting with a 10-year time window; The included studies were those whose research was carried out in human beings, children, with indicators of speech production associated with stuttering and their rehabilitation processes. RE-SULTS: currently, Speech-Language Professionals in Latin America are adopting the empirical and praxis-based form, various rehabilitation strategies for users with impaired verbal fluency, adapted for the rehabilitation of the speech pattern of population stuttering European infant, however scientific evidence demonstrates the efficiency and effectiveness of a treatment method described in the Lid-combe program. ANALYSIS AND DISCUSSION: for the infant, fluent verbal language is of utmost importance, it is there where the need of the speech pathologist to seek standardized strategies that guarantee the complete rehabilitation of pathological speech mechanisms. CONCLUSIONS: the-oretical support determines that there are few rehabilitation methods for the intervention of child stuttering that are easily accessible for therapists, among them will be one that allows treating the speech characteristics of the Australian child population and that has been applied and adapted in some countries on the European and Asian continent.
Keywords: Speech; Stuttering; verbal fluenc; rehabilitation; child population